Garut Flash Flood Victim's Families: Relation Between Stress Management and Family Resilience Based on Residence and Post-disaster Time: Garut Flash Flood Victim's Families: Relation Between Stress Management and Family Resilience Based on Residence and Post-disaster Time - Euis Sunarti; Marwiah; Siti Badaria; Intan Islamia (Journal of Family Sciences, 2021)
This research aimed to analyze stress management (stressors, coping strategies, and stress symptoms) and family resilience (process and output) of garut flash flood victim families at 1 and 4 months post-disaster. This cross-sectional study involved 120 families (each 60 from the temporary shelter (FTS) and nontemporary shelter (FNTS)) who were chosen by stratified non-proportional random sampling. The results showed that FNTS faced higher stressors and did higher coping strategies than FTS, either at 1 or 4 months post-disaster. Stress symptoms were also higher among FNTS at 1-month post-disaster, while the output of family resilience was higher in FTS at 4 months post-disaster. Stressors significantly influenced stress symptoms at 1-month post-disaster, coping strategies and the process of family resilience. In contrast, stressors influenced stress symptoms at 4 months post-disaster, coping strategies and stress symptoms 1-month post-disaster. The process of family resilience influenced the output of family resilience at 1-month post-disaster. In contrast, the output of family resilience at 4 month post-disaster was influenced by residence, family income per capita, stressors and the process of family resilience. This study reinforces the importance of family resilience in disaster-prone areas.